An equilibrium wall model for reacting turbulent flows with heat transfer. (October 2019) - Muto, Daiki; Daimon, Yu; Shimizu, Taro; Negishi, Hideyo
Highlights: A new wall model including effects of chemical reactions is proposed. The wall model numerically solves equilibrium boundary layer equations. A table look-up is employed to estimate chemical effects and gas properties. The proposed model well predicts wall shear stress and heat flux in reacting flows. The present ODE-based wall model is superior to wall function models. Abstract: A wall model for reacting turbulent flows for predicting heat transfer in rocket engine combustion chambers is presented. The wall model is developed based on boundary layer equations and includes the effects of chemical reactions and variable properties. Assuming an equilibrium state near the wall, a simple set of momentum and enthalpy equation is formulated. A table look-up procedure is employed to calculate the contributions of chemical effects and mixture properties. For turbulence modeling of the inner layer, a modified mixing length model based on semi-local scaling is applied. The proposed equilibrium wall model is validated in two hydrogen/oxygen reacting cases. In the first validation case of a reacting turbulent channel flow, the equilibrium wall model accurately predicts the near-wall velocity and temperature fields. In contrast, the wall model when assuming frozen chemistry shows a discrepancy in temperature gradient and mixture properties. The heat flux balance in the equilibrium wall model highlights the important contributions of chemical effects. The second test case of a rocket combustion chamber shows that the equilibrium wall model is superior to the frozen wall model and wall function models in predicting wall shear stress and heat flux.